The association between carbon monoxide and cardiovascular-kidney-metabolic syndrome in the Chinese populations: China Health and Retirement Longitudinal Study - Xuemin Yin; Xi Fang; Yinjun Liao (Journal of Nephrology, 2026)
Abstract Background Cardiovascular-kidney-metabolic (CKM) syndrome is characterized by both high prevalence and mortality rates. Air pollution, a recognized risk factor for cardiovascular disease and a key component of CKM syndrome has been insufficiently studied in relation to CKM outcomes, particularly in Chinese populations. Methods This study leveraged the China Health and Retirement Longitudinal Study (CHARLS) database to investigate associations between major air pollutants, such as carbon monoxide (CO), fine particulate matter (PM2.5), respirable particulate matter (PM10), Nitrogen dioxide (NO2), Sulfur dioxide (SO2), and Ozone (O3), and CKM syndrome among 7569 Chinese adults. Correlations were assessed using logistic regression, while potential confounders were identified through subgroup analyses, and trends in variable relationships were visualized with restricted cubic spline curves. Results The results revealed that CO exposure is significantly associated with CKM syndrome prevalence, with adjusted odds ratio (OR) of 1.12 and 95% confidence interval (CI): (1.03,1.23), while other air pollutants showed no significant associations with CKM syndrome. The relationship between CO and CKM syndrome was modulated by factors such as older age, and education level. Conclusions These results underscore CO as a potentially modifiable factor requiring prospective validation for CKM syndrome in the Chinese population, and provide foundational evidence for future research exploring the preventive effect of CO mitigation on this syndrome.